Metabolic changes in siamweed, Chromolaena odorata induced by feeding of weed killer, Pareuchaetes pseudoinsulata (Arctiidae: Lepidoptera) - Lyla, K.R.; Abraham, C.C.; Joy, P.J. (Journal of Tropical Agriculture, 2006)
The arctiid caterpillar, Pareuchaetes pseudoinsulata Rego Barros, has been identified as a potential bio-control agent of the Siam weed, Chromolaena odorata King and Robinson. The present studies were to assess the metabolic changes in the plants induced by larval feeding. The total nitrogen content in leaf samples showed significant variations on 4th, 6th, 8th, 10th, 12th, and 15th days after releasing variable number of Pareuchaetes larvae. Total nitrogen was maximum in the leaves, on the sixth day of release of four larvae per plant. Leaf nitrogen showed a declining trend when the larval load per plant was increased from the eighth day of release onwards. The nitrogen content was the least on 15th day after release of twelve larvae. Nitrate nitrogen content showed an increasing trend with increasing number of larvae and days after release. Chlorophyll content in the leaves got reduced significantly with increased larval population load in plants and with the passage of time of confinement of larvae.